Organic Waste Recycling Technology and Management - Third Edition - Polprasert, Chongrak (IWA Publishing, 2007)
"This book covers the principles and practices of technologies for the control of pollution originating from organic wastes (e.g. human faeces and urine, wastewater, solid wastes, animal manure and agro-industrial wastes) and the recycling of these organic wastes into valuable products such as fertilizer, biofuels, algal and fish protein and irrigated crops. Each recycling technology is described with respect to: - Objectives - Benefits and limitations - Environmental requirements - Design criteria of the process - Use of the recycled products - Public health aspects. Organic Waste Recycling includes case studies, examples, exercises and questions. This book is intended as a text or reference book for third or fourth year undergraduate students interested in environmental science, engineering and management, and graduate students working in the environment-related disciplines. It also serves as a reference text for policy makers, planners and professionals working in the environment and sustainable development fields."